Social exclusion: differences in neural mechanisms underlying direct versus vicarious experience - Song, Juan; Lian, Tao; Zhang, Yunhong; Cao, Mingjing; Jiao, Zhibin (Frontiers in Psychology, 2024)
Social exclusion stands as a source of social discord and holds substantial research value. Prior investigations on social exclusion have overlooked the interactive relationship between the excluded individuals and the observers. Hence, this study comparatively explores the neural mechanisms underlying the psychological responses of two distinct roles within the same social exclusion context. A total of 40 35 pairs (20 19 pairs of females) participated in the experiment. Within each pair, one individual assumed the role of a socially excluded participant (subjecttarget), while the other acted as a social exclusion observer. SubjectTargets engaged in an online ball-passing game where controlled ball allocations to the participants created an exclusion scenario. Meanwhile, observers spectated the subjecttargets playing the game. Throughout the ball-passing activity, functional near-infrared spectroscopy (fNIRS) recorded the blood oxygen data in the prefrontal cortex (PFC) and temporoparietal junction (TPJ) of both participants. Our findings revealed varied levels of rejection sensitivity elicited by direct or observed social exclusion experiences. Additionally, distinct patterns of neural activation were observed: subjecttargets displayed conditional differences in the medial prefrontal cortex (mPFC), while male observers exhibited conditional activation differences in the mPFC, and female observers showed conditional activation differences in the right dorsolateral prefrontal cortex (dlPFC). This study juxtaposes the behavioral and neural activation variances between subjecttargets and observers within the same social context, offering a novel perspective on investigating the neural mechanisms of social exclusion.